From Reel World vs. Real World: Are We Raising a Generation Detached from Reality? - Dr. Pallavi Dubey (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Social media has revolutionized communication and information sharing, but it has also brought psychological and social challenges. This study explores the phenomenon of "Social Media Hangover," which is mental fatigue, emotional distress, and social detachment resulting from excessive use. This can lead to anxiety, reduced productivity, and a di-minished emotional well-being. This study identifies gaps in understanding this phenomenon and emphasizes the need for sustainable solutions. This study provides actionable insights for promoting healthier social media use, in-cluding digital mindfulness, digital detoxes, and educational programs. This study urges individuals, educators, and policymakers to proactively address the implications of Social Media Hangover and encourages further research to ex-plore effective interventions.